Inhibition of Caco3 Growth and Synthesis of Submicron Particles by Preferential Adsorption of Additive Ca2+ Ions on Fresh Precipitates - Majekodunmi, Olukayode T.; Kılıç Özdemir, Sevgi; Özdemir, Ekrem; Özdemir, Ekrem; Kılıç Özdemir, Sevgi (Royal Society of Chemistry, 2022)
This study demonstrates a method to inhibit the growth of CaCO3 and synthesize submicron particles in a chemical precipitation process under ambient and high supersaturation conditions. Equimolar CaCl2 and Na2CO3 solutions were mixed in a model tubular reactor at a constant flow rate, and the precipitates were continuously dispersed in stirred 250 mL of 10 mM Ca(OH)2 solution. This approach resulted in the synthesis of colloidally stable submicron CaCO3 particles for a precipitant concentration ≤75 mM. Varying the precipitates’ retention time in the tubular reactor had no significant effects on the particle size and colloidal stability. Time-dependent changes in the mean size, crystal form, morphology and specific surface area of the synthesized particles were also studied. For a precipitant concentration of 75 mM, the particles were monodispersed and porous spindle-like scalenohedral crystals which gradually grew in all faces as more precipitates were fed into the Ca(OH)2 solution. The mean hydrodynamic size of the particles was ∼850 nm at the 8th minute. However, in the absence of additive Ca2+ ions, the particles obtained at the 8th minute were polydisperse mixtures of vaterite and rhombohedral calcite particles greater than 4 μm in size. The results show that free additive Ca2+ ions are irreversibly adsorbed onto the particles as the precipitates dissolve and recrystallize into smaller crystals upon reaching the Ca(OH)2 solution.
Keywords: Calcite; Calcium carbonate; Chlorine compounds; Additives